Artificial intelligence applied to the management of dyslexia cases in university settings: A systematic review - Marín-González, Freddy; Cuba-Romero, Gabriela Cristina; Larios-Ariza, Michell Andrea (Revista de Ciencias Sociales, 2025)
Dyslexia is a learning difficulty that affects reading and writing and has been studied in search of novel tools for detection and treatment. This article analyzes the applicability of Artificial Intelligence to the management of dyslexia cases in university settings, through a systematic review focused on the contributions of scientific literature on assessment/diagnosis and intervention processes. Through searches in Scopus and Web of Science, empirical studies were selected considering the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Protocols method. The results show that Artificial Intelligence is effective in the detection of dyslexia through eye movement analysis and neuroimaging, allowing early diagnosis. However, research has mainly focused on assessment and diagnosis, while its application in interventions requires further study. In conclusion, Artificial Intelligence has the potential to improve accessibility and personalization in the treatment of dyslexia, contributing to the transformation of university educational processes in students suffering from this condition.